Performance and characterization of phenol-formaldehyde resin with crude bio-oil by model compound method - Yu, Yuxiang; Qiu, Xiaoqian; Li, Chao; Bao, Defu; Chang, Jianmin (PloS one, 2023)
In order to clarify the effects of crude bio-oil for phenol-formaldehyde resin, the phenol-formaldehyde resin with bio-oil model compounds (BMPF) were prepared by model compound method. The bonding strength and aging resistance of BMPF were determined, and their microstructure and chemical bonds were also analyzed by scanning electron microscope, Fourier transform infrared spectroscopy, and nuclear magnetic resonance analysis, respectively. The results showed that the components of crude bio-oil had various degrees of effects on the BMPF performance, and the most obvious one is the phenols. The phenols and the ketones of bio-oil had positive effects on the bonding strength. The ketones had the biggest effect on the surface smoothness of BMPF film. But all components of bio-oil could inordinately improve the aging resistance of BMPF. The structural analysis indicated that the effects of bio-oil components on the BMPF performance by changing the resin structure. The CH 2 peak in FT-IR and the methylene bridges intensity in NMR of phenol-free BMPF and ketone-free BMPF were smaller, while the results of aldehyde-free BMPF and acid-free BMPF were opposite. And the influence degree of BMPF structure was basically consistent with that of BMPF performance. These results could provide a basis for the modification of phenol-formaldehyde resin by crude bio-oil.